EXTERNALITIES: A CRITIQUE OF FALSE REPRESENTATIONS - A. Otroshko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article refutes some of the misconceptions about the externalities. Particular attention is paid to the critical analysis of traditional approaches to the justification of the need for government intervention in markets in the case of externalities.